Welding sequence effects on residual stress distribution in offshore wind monopile structures - Ali Mehmanparast; Oyewole Adedipe; Feargal Brennan; Amir Chahardehi (Fracture and Structural Integrity)
Residual stresses are often inevitably introduced into the material during the fabrication processes, such as welding, and are known to have significant effects on the subsequent fatigue crack growth behavior of welded structures. In this paper, the importance of welding sequence on residual stress distribution in engineering components has been reviewed. In addition, the findings available in the literature have been used to provide an accurate interpretation of the fatigue crack growth data on specimens extracted from the welded plates employed in offshore wind monopile structures. The results have been discussed in terms of the role of welding sequence in damage inspection and structural integrity assessment of offshore renewable energy structures.